The Self-Esteem of The Elderly Through Line Application - Sunonthanam, Nawaphorn (Journal of The Royal Thai Army Nurses, 2020)
This research purpose to study factors that influence the self-esteem of the elderly through the LINE application, to compare the self-esteem of the elderly between using LINE application and using real-life experience, and to recommend the positive attitudes about self-esteem of the elderly through line application. The sample consisted of 385 people select the sample according to the qualifications. Questionnaires were used as a data collection tool. Data were analyzed using descriptive statistics and inferential statistics consist of independent T-tests, One-way ANOVA, Paired Samples T-Test and Pearson’s Product Moment Correlation Coefficient The study found that self-esteem of the elderly living alone was statistically significant lower than the elderly who did not live alone (p = .000). Frequency of using each function was found to have statistically significant relationship with level of self-esteem (p = .000). By comparing the total scores from the assessment between LINE application and real-life experience group, LINE application group statistical significance perceived more significant than real-life experience with mean 3.83 and 3.73, respectively (t = 2.715, p = .007). Recommendations for further research should be studied in other areas where the context is different. The government sector should increase the opportunity to access and awareness in LINE application. Private sectors use LINE application as a tool to enhance self-esteem of the elderly. Finally, the elderly should have proper use of the application line.